KAJIAN DISTRIBUSI SPASIAL DEBIT ALIRAN PERMUKAAN DI DAERAH ALIRAN SUNGAI (DAS) BERBASIS DATA SATELIT PENGINDERAAN JAUH - Trisakti, Bambang; Teguh, Kuncoro; Susanto, Susanto (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2008)
The aim of this paper is to analyze the spatial distribution of the water discharge in the Ciliwung watershed based on the remote sensing satellite data. Digital elevation model (DEM) is processed to determine the watershed border using the steepest slope method and also used to calculate pixels area. The calculated pixels area are used to determine the watershed and landcover areas in 3 dimension perspective, the landcover of the Ciliwung watershed is mapped by using SPOT-4 image acquired in 2007. All generated information are used as the input to determine the spatial distribution of the water discharge using the run-off coefficient table produced by related institutions. In the next step, the total water discharge in some outlets (Katulampa, Depok and Muara Ciliwung) are compared and the relationship between the landcover condition and the water discharge is evaluated. The result shows that DEM can be used to determine the watershed border and calculate the watershed area, which the results are almost same with the real condition. The spatial distribution of the water discharge is useful to analyse the water discharge contribution of each part of watershed to the total water discharge in the Ciliwung watershed. It shows that the water discharge in Katulampa outlet contributes 44 % of the total water discharge in the Ciliwung watershed. Further, some landcover types are identified in the high water discharge area. This kind of information is very useful for the regional planning and flood management activities.